Analytical Studies of the Excitation System of Synchronous Generator in Steam Power Plant Unit 3 and 4 at PJB UP Gresik - Pamungkas, Rizky Catur; Mustar, Muhamad Yusvin; Syahputra, Ramadoni (Journal of Electrical Technology UMY, 2017)
Generator or alternator is a device that has a function to convert or transformmechanic energy to electricity. Electricity conversion need process with givingstrengthening with excitation current to coil magnetic field that placed on sync generator. Excitation current that flows on magnetic field coil will cause magnetic flux. Generator sync on PLTU unit 3 and 4 PJB UP Gresik use excitation system with excitation static type, this type of excitation it uses carbon brush as a media to conduct excitation current, this excitation system use the output of sync generator. In reality this excitation current which exist on PLTU unit 3 and 4 have to should always be taken care so the system can operate normally and commonly the fault that happened is under excitation and over excitation so it can be prevent. Step taken to avoid damaging the generator sync that caused by excitation current, steps that have to be taken are understanding thecharacteristic of system excitation setting, anchor current, voltage generator, and loading. The value of loading is very affecting the value of excitation current that injected toÂ generator, the purpose of this process of excitation current injection is to maintain the stability from sync generator voltage so that the condition is staying on its normal condition.